Synthesis, characterization and theoretical study of amino acid-based magnetic molecularly imprinted polymer for recognition of sulfonamide drugs / Chen Lei - Chen, Lei (2015)

(untitled)
Sulfonamides antibiotics (SAs) are the oldest and among the most widely used antibacterial agent in the world. Due to its low cost and their relative efficacy in controlling some common bacterial related diseases, SAs have been widely used in various sectors. Since huge amount of SAs have been consumed every year, SAs have been released into the environment through various human activities. Among various classes of pharmaceutical, the presence of antibiotics in the environments has been one of the major concerns due to its ability to develop antibiotic-resistant bacteria. Thus, it is essential to develop an efficient method for the determination of SAs in the environment. The main objective of this study was to develop a multi-functional magnetic MIP for the extraction of SAs. The experiment was started from the computational study to design a suitable monomer for the multi-functional MIP. Based on the crystal structure of sulfamethoxazole (SMO) and dihydropteroate synthase, a serine-based monomer (Monomer-2) was designed and synthesized for this study. The performance of magnetic serine-based MIP (SMIP) was then compared with magnetic acrylamide-based MIP (AMIP). In this case, serine is an amino acid whereas acrylamide is a common commercially available monomer. The experimental study was started from the preparation of AMIP and followed by the evaluation of the performance of AMIP. The acrylamide-based MIP was imprinted directly onto the surface of MPS-modified MION. The result showed that the obtained AMIP possessed adsorption kinetics with 400 s to reach equilibrium. The results also indicated that the maximum adsorption capacity of 775 μg g-1 was achieved. Langmuir adsorption isotherm model was found to describe well the equilibrium adsorption data. The results from the iv competitive binding experiment showed that AMIP was not only selective towards sulfadiazine as the adsorption of sulfamerazine was dramatically high. Sulfadiazine and sulfamerazine have almost similar sub-structure where these two compounds were only differentiated by one methyl group. In order to explain this result, computational study was carried out. From different level of calculation with PM3, HF, and DFT calculation, both sulfadiazine and sulfamerazine showed similar interaction energy and mechanism with acrylamide monomer. This result indicated that, both sulfadiazine and sulfamerazine could have the same binding property in the AMIP. By using the similar approach as AMIP, SMIP was synthesized. As compared to the AMIP, SMIP showed a faster adsorption rate on sulfadiazine with only 200 s to reach equilibrium level. The maximum adsorption capacity of SMIP was around 1547 μg g-1. This result is in agreement with the computational study. The computational study indicated that Monomer-2 (serine-based monomer) showed more favorable interaction with template as compared with acrylamide. Importantly, in the selectivity experiment, SMIP showed overwhelming advantage in the recognition of different SAs with the presence of 2 structural unrelated compounds. Therefore, it can be concluded that the multifunctional magnetic MIP can be designed by using computer modelling method. Amino acid based monomer can be used for the preparation of MIP and this MIP showed the characteristic that mimic to the ligand-enzyme interaction.